Rapid growth and large body size in annual fish populations are compromised by density-dependent regulation - Vrtílek, Milan; Žák, Jakub; Polačik, Matej; Blažek, Radim; Reichard, Martin (Journal of fish biology, 2019)
We tested the effect of population density on maximum body size in three sympatric species of annual killifishes Nothobranchius spp. from African ephemeral pools. We found a clear negative effect of population density on body size, limiting their capacity for extremely fast development and rapid growth. This suggests that density-dependent population regulation and the ephemeral character of their habitat impose contrasting selective pressures on the life history of annual killifishes.
Keywords: Sex Factors; Cyprinodontiformes; Population Density; Nothobranchius; Ecosystem; Female; hustota populace; sympatry; temporary habitat; velikost těla; zvířata; plasticity; sexuální faktory; Africa; věkové rozložení; population regulation; roční období; ženské pohlaví; Male; Afrika; somatic growth; Seasons; Mosambik; Age Distribution; Body Size; Mozambique; Animals; mužské pohlaví; ekosystém; Fundulidae